Rapid-deposited high-performance submicron encapsulation film with in situ plasma oxidized Al layer inserted. (1st April 2022) - Qin, Houyun; Liu, Chang; Peng, Chong; Lu, Mingxin; Liu, Yiming; Wei, Song; Wang, Hongbo; Yue, Nailin; Zhang, Wei; Zhao, Yi
Abstract: High-performance submicron thin-film encapsulation deposited rapidly under low temperature plays an important role in Si-based organic micro-displays. In this letter, the formation mechanism of high-performance encapsulation films consisting of SiO2 /in situ plasma oxidized Al at 77 °C is explained. We think that the reason why the performance of encapsulation films deposited by this method behave better than the simple stacking of SiO2 /Al2 O3 is the formation of Al–O–Si bonds. By further optimizing the process parameters, the water vapor transmission rate and the transmittance in the visible region have been improved, which reached 10 −6 g∙m −2 ∙d −1 and 90%, respectively.